Safety Evaluation of Skin Care Products for Hypersensitive Skin - SASAI, Shu; TAGAMI, Hachiro; O'GOSHI, Ken-ichiro (Skin research, 2000)
We carried out the occlusive patch tests for three NOV® cosmetic products (Whitening Essence N®, Moisturizing Essence N®) and Moisturizing Pack N® in order to evaluate the safety to the skin. Subjects were 67 patients who experienced some skin troubles including xeroderma, contact dermatitis, atopic dermatitis and photosensitivity. These samples were applied to the mid volar forearms for 48 hours. The concentrations of these samples were those of “as is” with white petrolatum and distilled water being used as controls.The irritation index ranged from 0.7 to 8.2 and the highest number was 8.2 for Whitening Essence N® and for Moisturizing Essence N®. The results indicate that these cosmetic products show high safety even for hypersensitive skin.